PERAN STRATEGIS ALUN-ALUN PURWOKERTO DALAM MENINGKATKAN AKTIVITAS EKONOMI DAN KESEJAHTERAAN MASYARAKAT SEKITAR - Nida Nurlailia Putri; Futi Khatussolikhah; Nur Zahra Alya Nabila; Yoiz Shofwa Shafrani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
One of the concept of urban governance is the existence of public spaces. Purwokerto Square is a publics space that is well known to the community and plays a crucial role in supporting the social and economic sectors in the city center. Through a descriptive qualitative approach that includes a literature review and contextuan case studies, this study aims to analyze the contribution of Puwokerto Square in improving local economic activity and community welfare. The result of this study show that the square not only function as a means of recreation and social activities, but also as an economic center that encourages th growth of the UMKM sector, create jobs, and increases community income. However, there are still obtacles suc as limited infrastructure and suboptimal management.